2017
DOI: 10.1080/02699052.2017.1332388
|View full text |Cite
|
Sign up to set email alerts
|

Reducing concussion symptoms among teenage youth: Evaluation of a mobile health app

Abstract: Objective To evaluate whether a mobile health application that employs elements of social game design could compliment medical care for unresolved concussion symptoms. Design Phase I and Phase II (open-label, non-randomized, ecological momentary assessment methodology). Setting Outpatient concussion clinic. Participants Youth, aged 13–18 years, with concussion symptoms 3+ weeks after injury; Phase I: n = 20; Phase II: n = 19. Interventions Participants received standard of care for concussion. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Most studies were conducted in a real-world setting, such as at home or in school locations. Other contexts included emergency rooms [ 44 , 45 ], medical clinics [ 50 ] or hospitals [ 43 ], and commuting settings [ 28 ]. A variety of different program delivery methods (eg, apps, monitoring programs, text messages, videos) were reported among the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies were conducted in a real-world setting, such as at home or in school locations. Other contexts included emergency rooms [ 44 , 45 ], medical clinics [ 50 ] or hospitals [ 43 ], and commuting settings [ 28 ]. A variety of different program delivery methods (eg, apps, monitoring programs, text messages, videos) were reported among the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive behavioral therapy (CBT) was the most commonly reported treatment, with 5 studies noting its use. Other treatments listed were attention bias modification [ 27 ], emotional self-awareness [ 42 ], and positive psychology, social interaction, and gameful design [ 50 ]. Among the CBT-centered interventions, specific features included concepts such as emotional regulation [ 45 ], thought modification [ 44 ], photo libraries of positive memories and physical activities [ 47 ], video diary messages [ 49 ], and psychoeducation [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some efforts have been made, as indicated in the literature, to develop and evaluate apps for pediatric concussion management. For example, a study [20] evaluated the effects of a gamified mobile phone app in promoting health management in teenagers with persistent postconcussion symptoms, and it showed promising initial results for the use of mobile phone apps for the management of postconcussion syndrome [20]. However, this app focuses on improving the management of postconcussion syndrome that is experienced by only a subset of all concussed youth [21], and the app does not provide guidance throughout the entire recovery process, thus missing the opportunity to be preventative and guide youth from the onset of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to intervention compliance should also be considered. Although not included in the final review, Worthen-Chaudhari et al [55] reported on barriers to study compliance and found that participants who dropped out of the study had discontinued medical care, faced problems with internet access, busy schedules, and experienced co-occurring illness during the study. Although these factors were not assessed after completion of the intervention, it is important to consider these as potential barriers to intervention usage that could affect study results.…”
Section: Discussionmentioning
confidence: 99%